Debendox and congenital malformations in Northern Ireland. Issue 6252 (22nd November 1980) - Harron, D W; Griffiths, K; Shanks, R G
Abstract : An investigation was carried out in Northern Ireland into the alleged association between fetal abnormalities and Debendox, an antiemetic drug used in pregnancy. During the period 1966-78 the total number of births each year and the overall incidence of congenital malformations per 10 000 births fell. The incidences of cleft lip, cleft palate, reduction deformities, and defects of the heart and great vessels fell from 1966 to 1976 but increased in 1977 and 1978. During the same period (1966-78) the number of prescriptions for Debendox issued by general practitioners increased more than fourfold. These observations suggest that there is no relation between congenital malformations and the use of Debendox. This conclusion, however, does not take into account other drug- or environmental-related factors that may have resulted in a reduction in the number of congenital malformations and would hence have masked an increase associated with greater usage of Debendox. In particular, the amount of Debendox sold direct to the public without a prescription and the use of the drug by patients who were not pregnant could not be established. The amount of drug used in these ways is probably small, and it is difficult to see how it might influence the conclusions reached.